Iniciativas de restauração de paisagens e florestas com agricultores familiares da reforma agrária em um assentamento rural no Vale do Paraíba Paulista - Pereira, João Carlos Mendes (Universidade Federal de São Carlos, 2025)
Since the large-scale occupation process, the Vale do Paraíba Paulista (VPP) region has faced significant changes in its landscape, resulting in environmental degradation and the loss of essential ecosystem services. To change this scenario, landscape and forest restoration (FLR) has been adopted as an effective strategy to mitigate the historical damage caused by the occupation of the region, especially in land reform settlements. However, the characteristics of these initiatives, the motivations of farming families and their effects on the agro-ecosystem have been little studied. The aim of this study was to characterize and analyse FLR initiatives carried out by agrarian reform family farmers in a rural settlement located in the VPP region, with a focus on potential improvements in the agro-ecosystems of the settled families. Semi-structured interviews with family farmers were used to collect qualitative data, along with questionnaires and farm visits. The data was analyzed using content analysis and descriptive statistics. Most of the interviewees who do catering are from urban areas and have a higher level of education. Among the strategies adopted, agroforestry systems stood out as the most common option among the families, implemented through community efforts. The main motivation for the families' involvement in restoration was the recovery and preservation of water. Increased biodiversity, improved soil, changes to the plot's landscape and the recovery of water resources were the main effects of restoration on the agro-ecosystem perceived by the families interviewed. The results of the research indicate that RPF, through agroforestry systems, has generated positive effects for family agroecosystems and presents itself as an effective way of enabling food production and simultaneously restoring degraded areas in rural settlements.
Landscape and forest restoration initiatives with agrarian reform family farmers in a rural settlement in São Paulo's Paraíba Valley
Iniciativas de restauración paisajística y forestal con agricultores familiares de la reforma agraria en un asentamiento rural del valle del Paraíba en São Paulo
Keywords: Agricultura Familiar; Family farming; Agroecossistemas; Assentamentos de reforma agrária; Restauração Florestal; Agroecosystems; Agrarian reform settlements; Forest restoration; Agroforestry systems; Sistemas agroflorestais; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL